The Impact of Service Quality Dimensions on Performance: An Empirical Investigation of Jordan's Commercial Banks - Mamoun N. Akroush; Fahed S. Khatib (Journal of Accounting, Business and Management (JABM), 2009)
The aim of this research is to examine the relationship between service quality dimensions (functional and technical) and banks performance assessed based on financial performance and customer indicators. A quantitative methodology was employed to test a model of service quality which was developed for the purpose of this study. The research data were collected from managers' perspectives working for banks operating in Jordan. The sample size was 390 managers working at Jordans commercial banks headquarters. Multiple regression analysis and ANOVA statistical tests were employed to test the research model and hypotheses. The research findings indicate that the service quality dimensions (functional and technical) have positively and significantly affected banks performance assessed based on financial performance and customer indicators. The functional quality dimension has a stronger effect on all banks performance indicators than the technical quality dimension. The effect of service quality dimensions (functional and technical) on the banks financial performance is still stronger than their effects on banks customer indicators. Research findings, conclusions and implications, contribution to knowledge as well as future research were also discussed.